2001
DOI: 10.1136/qhc.10.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with out of hours primary medical care

Abstract: Objectives-To describe the relationship between patient satisfaction with out of hours care provided by deputising and practice doctors in four urban areas in England and characteristics of the service provided and patients, the care given, and health outcomes. Setting-Fourteen general practices in four urban areas in England. Participants-People who requested out of hours care. Design-Analysis of data from a study of out of hours care. Patients were interviewed within 5 days of their request for out of hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 14 publications
3
45
0
1
Order By: Relevance
“…Age 12,20,21 is usually associated with dissatisfaction with health services and this study emphasized the findings present in related literature. The dissatisfaction is smaller in the elders.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Age 12,20,21 is usually associated with dissatisfaction with health services and this study emphasized the findings present in related literature. The dissatisfaction is smaller in the elders.…”
Section: Discussionsupporting
confidence: 62%
“…The satisfaction with emergency health services has mainly been associated with physical comfort, medical and nursing care 18,19 , gender, place of residence, civil status, income 20 , education, and age 20,21 . A meta-analysis based on performance results from Iran's emergency health services showed that users are reasonably satisfied (70.9%) 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Although the 'disconfirmation of expectations' comprises one of the main theoretical models of consumer satisfaction, 9 empirical studies show that the relationship between satisfaction and expectations in healthcare is far from simple. [10][11][12] However, surveys of primary care walk-in patients 13 and of out-of-hours primary care patients 14,15 have shown that, in these patient groups, decreased satisfaction with the consultation is associated with unmet expectations. A recent qualitative study of dental patients has also reasserted the importance of expectations in determining satisfaction with dental care.…”
Section: Introductionmentioning
confidence: 99%
“…'Universal access' services -intended for both registered and unregistered patients -exist in some areas, and these may use either telephone-based or 'walk-in' access arrangements, and see patients in either hospital, NHS community dental service (CDS) or general dental surgery settings. 1 Despite this diversity in the types of out-of-hours dental care available, and a wealth of studies of different models of GP-provided out-of-hours medical care, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] there are no comparative studies that assess the effectiveness of emergency dental care provided in different ways. This study was originally designed to compare the cost-effectiveness of 'universal-access' out-of-hours dental care arrangements with 'conventional' out-of-hours care (that is, arrangements where there are separate service arrangements for registered and unregistered patients).…”
Section: Introductionmentioning
confidence: 99%